PERSEPSI MASYARAKAT PEKANBARU TERHADAP TEMPAT CLUB EXECUTIVE KARAOKE DI JALAN SUDIRMAN, KOTA PEKANBARU - Raditya Trisna; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Pekanbaru city experienced rapid growth, this is because the city of Pekanbaru isthe capital of Riau province so pembangungan concentration centered in the city ofPekanbaru is a strategic place for karaoke entertainment industry in particular, is due to thelack of tourist attractions in the city of Pekanbaru, while the level of community mobility ishigh enough, so there was nightspots in the community such as Club executive Karaoke,public interest in visiting Club Executive Karaoke quite high. Opportunity is that capturedthe investors to invest in competing karaoke entertainment industry in particular, be it afamily or club executive karaoke karaoke.The purpose of this study is to describe the public perception of the Club ExecutiveKaraoke in the city of Pekanbaru and to determine the impact of Club Executive Karaokefor the city of Pekanbaru.The method used in this research is descriptive qualitative method is to describe andexplain the results of research in the form of words spoken or written on a number ofqualitative data. The location of this research was conducted in Jalan Sudirman PekanbaruBased on the results of research conducted in the field, a positive public perceptionof the Club Executive Karaoke namely as a means of family entertainment. As for thenegative public perception of the Club Executive is not only as a family entertainment butserve adult entertainment establishments selling alcoholic beverages, narcotics and providecomfort women so that visitors are free to do anything that is no longer compatible with therules and norms of society. Presence Club Regional Executive Karaoke violate regulations(Government) NO.3 of 2002 on Public Entertainment In Chapter III Section 4 of theentertainment licensing regulations and entertainment Club Executive Karaoke alsoviolated Section IV, Article 5 of the operational time entertainment venues. To overcomethis Pekanbaru city government must be firm in overseeing the entertainment venues thathave violated the rules of the area.Keywords: Perception, Society, Club Executive Karaoke